Influence of Double Entry Volute on Incidence Angle Variation Under Steady Flow: Numerical Investigation - Gurunathan, Balamurugan A; Khairuddin, Uswah; Azlan Shah, Nazrun Nabill; Martinez-Botas, Ricardo (CFD Letters, 2020)
EGR extraction from one side of the exhaust manifold creates imbalance of mass flow in a double entry turbine. To overcome this problem, the asymmetric double entry turbine was introduced. The performance maps of this turbine were obtained through extensive test configurations in both steady and unsteady flow conditions at Imperial College cold flow test rig. Two main configurations were investigated; nozzleless and nozzle vane setting. Nevertheless, no attempt has been made to compare the performance of asymmetric double entry turbine to that of the symmetric counterpart. One way to make comparison between these two double entry turbine volutes, is by using numerical simulation. This is achieved by using ANSYS CFX tool in this paper. A symmetric double entry volute CAD model is developed using the same A/R ratio as the asymmetric counterpart, adopting the same mixed flow rotor, inlet and exit ducts. The steady state numerical investigation was conducted at two turbine speeds, 30k RPM and 48k RPM, for the nozzleless configuration. Steady state experimental results of asymmetric double entry turbine are set as the boundary condition in the simulation. Validation of the simulation results with that of the experimental data, shows good agreements for both speed lines for the asymmetric double entry turbine. The symmetric double entry turbine recorded peak efficiencies; lower by 2.8% and 8%, at 30k RPM and 48k RPM respectively, compared to that of asymmetric double entry turbine. The results of steady state conditions of the asymmetric double entry turbine suggest that the distribution of the incidence angle is better than the symmetric double entry turbine as it is able to maintain the incidence angle at off-design and design point operating condition within the same range.